Perbandingan Specific Refining Energy pada Mesin Refiner Jenis Double Disk dengan Conical: Studi Kasus pada Pembuatan Kertas Tulis Cetak - Susantini, Ni Njoman Manik; Pinasih, Intan; Erwin, Erwin; Hanifadinna, Hanifadinna (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2024)
The refining process is a part of the paper-making process that requires a large amount of energy. The strategy used is to change the type of refiner machine from Conical to Double Disc Refiner (DDR) because DDR spends less energy. At a consistent range of 4% Specific Edge Load (SEL) DDR is 1.4–4 J/m while conical SEL is 0.9–6.0 J/m. This research will test the energy used in making HVS paper 80-gram by referring to what has been mentioned. The consistency used is in the range of 4.4–4.6%. As supporting parameters, the physical properties of HVS 80-gram paper were used, namely bulk, tearing, tensile, and bursting. Energy and physical properties were measured for 28 days with 6 samplings per day. The comparison was carried out on days 10 to 26 because there was incomplete data on DDR on days 7–9 and day 27. The results of this study showed that the type replacement from conical to DDR was at 1.52%. The physical property of the paper that experienced a significant change was the paper porosity, which was 28.58%.